Issues and Challenges Faced by Persons with Disabilities in Basco, Batanes - Billote, William Jo Se; Ponce, Ryan; Ponce, Trixie Elaine; Arca, Julie Melanie; Cabrito, Ma. Kimberly Christine; Candel, Cristine Joy; Dasig, Charleth; Gato, Lyca Jade; Regidor, Ira Nicole; Zabala, Victor Jacob (JPAIR Multidisciplinary Research, 2022)
Persons with disabilities (PWDs) are one of the concerns of society. But due to prejudice, they are put in a disadvantageous position. Since then, there have always been issues in employment, social roles, and accessibility to education. These have led to self-doubt and inferiority, resulting in negative attitudes from non-PWDs. The study aimed to explore the issues and challenges faced by persons with disabilities in Basco, Batanes, Philippines. This study used a qualitative research design. The researchers used purposive sampling and gathered data from eight (8) qualified participants. The researchers determined the issues and challenges they faced across the four areas of their lives. First, they face difficulties at work and looking for work because of their condition and the prejudice they receive in the work environment. Second, they faced problems in school due to poverty and discrimination from classmates. Third, they receive discrimination and stereotyping from their community. Lastly, the majority of the participants receive support from their families. However, they also faced financial problems, especially with their medication.